Eksplorasi dan Identifikasi Agen Antagonis dari Lahan Organik Sebagai Implementasi Pengendalian Hayati - Miftahurohman, Muhammad; Utari, Amilia Ayu Jen; Mahendra, I Gede Rio; Simbolon, Novita Dong Mariris; Annisa, Septina Nur; Nuryanti, Ni Siluh Putu; Maharani, Juwita Suri; Budiarti, Lina; Priyadi, Priyadi (Politeknik Negeri Lampung, 2024)
The agricultural sector plays a strategic role in food security and environmental sustainability; however, it faces challenges such as declining productivity and pollution due to synthetic chemicals. This study aims to identify antagonistic fungi from organic lands and test their effectiveness in controlling Fusarium sp. pathogens as part of integrated pest management. The methods employed include exploration, isolation, identification, and antagonistic fungi testing on Potato Dextrose Agar (PDA) media. The results revealed four types of identified fungi, including light green, brown, and black, which belong to the Aspergillus sp. and dark green is Trichoderma sp. species. The light green antagonistic fungus effectively suppressed the growth of Fusarium pathogens by 57.84%, while the dark green fungus showed a suppression rate of 32.32%. This study emphasizes the potential of antagonistic fungi as effective biocontrol agents in sustainable agriculture.